SULT2B1: a novel therapeutic target in colorectal cancer via modulation of AKT/PKM2-mediated glycolysis and proliferation - Jianxing Ma; Fengyao Sun; Wen Li; Ruihang Du; Mingchan Liu; Qiuya Wei; Boxiong Kang; Siyuan Yan; Chen Wang (Journal of Translational Medicine)
Abstract Background Sulfotransferase family 2B member 1 (SULT2B1) is involved in regulating cell proliferation, migration and metabolism. However, there is still dispute regarding whether SULT2B1 acts as an oncogene or a suppressor, and the intrinsic mechanisms in modulating tumor progression need to be further elucidated. Methods This work aims to reveal the relationship among SULT2B1, AKT, PKM2 signaling and glycolytic pathways, and provided a theoretical basis for SULT2B1 as a potential therapeutic target for CRC.Bioinformatics methods, immunohistochemistry (IHC) and immunoblotting assays were performed to analyze the correlation between SULT2B1 and colorectal cancer (CRC). The effect of SULT2B1 on cell proliferation and migration were investigated by several phenotypic experiments in vitro and animal studies. The SULT2B1 interacting proteins were determined by immunofluorescence, immunoprecipitation and GST-pull down assays. Immunoblotting and mCherry-GFP-LC3 assays were performed to analysis autophagy. Chromatin immunoprecipitation (CHIP) assay was utilized to detect the effect of SULT2B1 in regulating transcription. Small molecule agonist/antagonist was used to modify protein activity and therefore analyze the mutual relationships. Results SULT2B1 is a predictive biomarker that is abnormally overexpressed in CRC tissues. Overexpression of SULT2B1 promoted cell proliferation and migration, while its knockout suppressed these processes. Furthermore, SULT2B1 could directly interact with the oncogene AKT and thereby enhance the activity of AKT-mTORC1 signaling. Furthermore, PKM2 was found to bind with SULT2B1, and regulated by SULT2B1 at both transcription and degradation levels. Moreover, blocking glycolysis attenuated the promoting effect of OE-SULT2B1. Conclusion SULT2B1 acts as an oncogene in CRC via modulating the AKT/PKM2 axis, therefore making it a promising diagnostic and therapeutic target for CRC.